The Role of miR-155 in Antitumor Immunity - Kalkusova, Katerina; Taborska, Pavla; Stakheev, Dmitry; Smrz, Daniel (Cancers, 2022)
MicroRNAs belong to a group of short non-coding RNA molecules that are involved in the regulation of gene expression at multiple levels. Their function was described two decades ago, and, since then, microRNAs have become a rapidly developing field of research. Their participation in the regulation of cellular processes, such as proliferation, apoptosis, cell growth, and migration, made microRNAs attractive for cancer research. Moreover, as a single microRNA can simultaneously target multiple molecules, microRNAs offer a unique advantage in regulating multiple cellular processes in different cell types. Many of these cell types are tumor cells and the cells of the immune system. One of the most studied microRNAs in the context of cancer and the immune system is miR-155. MiR-155 plays a role in modulating innate and adaptive immune mechanisms in distinct immune cell types. As such, miR-155 can be part of the communication between the tumor and immune cells and thus impact the process of tumor immunoediting. Several studies have already revealed its effect on antitumor immune responses, and the targeting of this molecule is increasingly implemented in cancer immunotherapy. In this review, we discuss the current knowledge of miR-155 in the regulation of antitumor immunity and the shaping of the tumor microenvironment, and the plausible implementation of miR-155 targeting in cancer therapy.
Keywords: microRNA; miR-155; tumors; immunity; immunotherapy; cancer